Infantile Idiopathic Intracranial Hypertension: A Case Study and Review of the Literature. (November 2019) - Boles, Sama; Martinez-Rios, Claudia; Tibussek, Daniel; Pohl, Daniela
Idiopathic intracranial hypertension, or pseudotumor cerebri, is an increase in cerebrospinal fluid pressure of unknown etiology. It is mostly seen in adults, less frequently in adolescents, rarely in younger children. Only 5 infants meeting idiopathic intracranial hypertension criteria have been mentioned in the literature. We report a case of a previously healthy 9-month-old boy who presented with irritability, decreased appetite, and a bulging fontanelle. Computed tomography (CT) head imaging and cerebrospinal fluid studies revealed normal results. The patient's symptoms transiently resolved after the initial lumbar puncture, but 11 days later, his fontanelle bulged again. A second lumbar puncture revealed an elevated opening pressure of 35 cmH2 O and led to a diagnosis of idiopathic intracranial hypertension in accordance with the modified Dandy Criteria. Treatment with acetazolamide at a dose of 25 mg/kg/d was initiated and the patient remained symptom-free for 6 weeks, followed by another relapse. His acetazolamide dose was increased to 37 mg/kg/d, with no further relapses to date. A diagnosis of idiopathic intracranial hypertension is challenging in infants, because the patients cannot yet verbalize typical idiopathic intracranial hypertension–related symptoms such as positional headaches, diplopia, or pulsatile tinnitus. Furthermore, it is more difficult to assess papilledema in that age group. If undetected and untreated, idiopathic intracranial hypertension may result in permanent visual deficits. Little is known about idiopathic intracranial hypertension in infants, and age-specific treatment guidelines are lacking. We discuss this rare case of infantile idiopathic intracranial hypertension and provide a review of the literature, including an overview of disease characteristics and outcomes of idiopathic intracranial hypertension in this very young age group.